Typhoid and paratyphoid fever co-infection in children from an urban slum of Delhi. (2020) - Dutta, Ankita; More, Deepak; Tupaki-Sreepurna, Ananya; Sinha, Bireshwar; Goyal, Nidhi; Rongsen-Chandola, Temsunaro
Abstract: We report two cases of co-infection with Salmonella Typhi and Salmonella Paratyphi A identified by blood culture and confirmed by serotyping from an ongoing fever surveillance cohort in an urban slum in New Delhi. Co-infections such as these have important implications on diagnosis, treatment options including choice of antimicrobial(s), disease outcome and strategy for prevention.